2017
DOI: 10.1371/journal.pone.0179945
|View full text |Cite
|
Sign up to set email alerts
|

Variation between the oral and faecal microbiota in a free-living passerine bird, the great tit (Parus major)

Abstract: The gastrointestinal tract of vertebrates is inhabited by diverse bacterial communities that induce marked effects on the host physiology and health status. The composition of the gastrointestinal microbiota is characterized by pronounced taxonomic and functional variability among different regions of the vertebrate gastrointestinal tract. Despite the relatively solid knowledge on the among-region variations of the gastrointestinal microbiota in model mammalian species, there are only a few studies concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 113 publications
(135 reference statements)
10
41
0
Order By: Relevance
“…We first demonstrated that digestive tract regions of wild P. major differ in gut microbial communities, but that these differences are not as prominent as previous studies have documented in other bird species [2,5,30,31]. While compositions differed between cloacal swabs and different gut regions, swabs qualitatively portrayed bacterial community compositions in the entire digestive tract, aligning with a previous study of wild birds [32], as well as reflected gut community compositions from a previous study of wild P. major fecal samples [16]. Microbial communities of alcohol-preserved gut regions did not differ significantly from fresh samples, supporting that museum collections represent a promising resource for analyses of gut microbiomes [37].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We first demonstrated that digestive tract regions of wild P. major differ in gut microbial communities, but that these differences are not as prominent as previous studies have documented in other bird species [2,5,30,31]. While compositions differed between cloacal swabs and different gut regions, swabs qualitatively portrayed bacterial community compositions in the entire digestive tract, aligning with a previous study of wild birds [32], as well as reflected gut community compositions from a previous study of wild P. major fecal samples [16]. Microbial communities of alcohol-preserved gut regions did not differ significantly from fresh samples, supporting that museum collections represent a promising resource for analyses of gut microbiomes [37].…”
Section: Discussionsupporting
confidence: 80%
“…Most bird microbiome studies have utilized feces [e.g., 11,13,14,[16][17][18][19][20] or cloacal swabs [e.g., [21][22][23][24][25][26][27][28][29], but a handful of studies have demonstrated that bacterial communities are compartmentalized across different digestive tract regions [2,5,30,31]. This questions whether non-invasive methods only capture fecal and cloacal bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on wild birds have demonstrated low bacterial diversity and community composition differences in the midgut region (stomach and small intestine) compared to the crop microbiota. This suggests that the highly-acidic conditions in the midgut region acts as a barrier for environmental and foodborne bacteria [14,66,76,77]. This is further evident when we look at previously published mealworm gut microbiomes [78], where only a small fraction of the microbiome consists of bacterial genera that we identi ed in the gut microbiomes of mealworm-fed P. major.…”
Section: P Major Gut Microbiomes Respond To Diet Changes But Not Asmentioning
confidence: 74%
“…On the other hand, S. saprophyticus is opportunistic pathogen causing inflammatory diseases of urinary tract in humans (Hovelius & Mårdh, ) and Dysgonomonas can cause gut inflammation in immunocompromised human subjects (Bangsborg, Frederiksen, & Bruun, ). Both these OTUs were previously detected in bird GM (Kropáčková, Pechmanová, et al., ; Kropáčková, Těšický, et al., ; Xenoulis et al., ). However, their effect on physiology and health of avian are still unknown.…”
Section: Resultsmentioning
confidence: 62%
“…However, Enterococcus genus includes also several pathogenic strains, whose infection can directly affect host's immunity (Fisher & Phillips, 2009 (Hovelius & Mårdh, 1984) and Dysgonomonas can cause gut inflammation in immunocompromised human subjects (Bangsborg, Frederiksen, & Bruun, 1990). Both these OTUs were previously detected in bird GM (Kropáčková, Pechmanová, et al, 2017;Kropáčková, Těšický, et al, 2017;Xenoulis et al, 2010). We propose that these seemingly contrasting results are related to both interaction complexity between bacteria and the verte-…”
Section: Re Sults and Discussionmentioning
confidence: 69%